TVET Sector Strategic Plan, 2023-2032: A Drive to Success - Lamsal, Hari Prasad; Bajracharya, Anil Muni (Journal of Technical and Vocational Education and Training, 2023)
The TVET sector faces a number of challenges, including declining enrollment, mismatch between supply and demand, and quality and relevance concerns. These issues may be addressed through a strategic plan that focuses on improving the quality of TVET programs, strengthening the governance and management of the sector, and increasing enrollment and participation. The three-phase 10-year plan in the article paves the path to address these challenges and move the TVET sector in the right direction. The first phase could focus on laying the foundation for a more effective and efficient TVET sector, including investment in infrastructure and technology, development of governance and management systems, and improvement of program quality. The second phase could focus on expanding access to TVET programs and increasing enrollment, while the third phase could focus on consolidating the gains made in the first two phases and making further improvements to the TVET sector. The author of this article conducted a desk review and engaged with various stakeholders to gain a comprehensive understanding of the challenges facing the TVET sector in Nepal. By identifying the current challenges and exploring the way forward through a 10-year plan in three phases, the article contributes to the development of a comprehensive and effective solution for the TVET sector. Overall, the article highlights the importance of a strategic approach to addressing the challenges facing the TVET sector in Nepal. By taking a phased, comprehensive approach, the TVET sector can be developed into a strong and effective source of economic growth and prosperity for the country.